The development of VGI application for urban road problems - Mojtaba Zeinali, 1985- author; Mohd. Safie Mohd., supervisor; Fakulti Geoinformasi dan Harta Tanah (2013)
Thesis (Sarjana Sains (Geoinformatik)) - Universiti Teknologi Nalaysia, 2013